Diversity of Caddisflies (Insecta: Trichoptera) in Pacho Waterfall, Budo-Su Ngai Padi National Park, Narathiwat Province - Teh, Nuro; Thawarorit, Kitiya; Suksupan, Pongpan (Princess of Naradhiwas University Journal, 2021)
The objective of this research was to study diversity of caddisflies in Pacho Waterfall, Budo-Su Ngai Padi National Park, Narathiwat Province. Field samplings were conducted during June to November 2017. Samples of the larvae were collected using a D-frame net and hand picking whereas those of the adults were collected using an ultraviolet light trap. Some physico-chemical parameters of water quality were also measured using water quality equipment. Three thousand, seven hundred and ninety-seven of larval individuals were found. Nine families and fourteen genera were found. Results of this study showed that the most abundant of larval caddisflies were found in June with 1,792 individuals. Hydropsychidae was the most diverse taxa included 5 genera while Hydropsyche, Chematopsyche and Chimarra were dominant and found at all collecting months. On the contrary, a few of individuals of Pseudoneureclipsis and Polycentropus were found. For their functional feeding groups, filtering collectors were more abundant (94.31%) than shredders (5.40%), Predators (0.16%) and gathering collectors (0.13%), respectively. Two hundred and sixty-six adult individuals were found included seven families, fourteen genera and twenty-five species were identified. The study of adults Hydropsychidae showed high diversity with 10 species, which Cheumatopsyche copia was both common and dominant and found almost every month of collection. Chimara bimbltona was the most abundant species.